When Citizens Are Minority: Toward Establishing A Comprehensive Emirati SME Support System (International Journal of Scientific Research and Management (IJSRM), 2018)
This paper endeavours to contribute to developing a comprehensive framework of institutional support system in a situation where citizens and citizen-owned SMEs form a minority in their own country. This is significant because it is not confined only to the case study of this Paper, (United Arab Emirates), but is prevalent in all countries of Gulf Cooperation Council. Examining the current situation of Emirati-owned SME reveals many challenges and opportunities. After developing an empirical framework for SME support and providing analysis of the Emirati SME scene, the paper uses the benchmarking approach (and Singapore has been selected for this purpose), and refers to other relevant literature, to discuss and develop constituents of the proposed support system. It concludes that Emirati SME support system may not be sustainable if not linked to a broader strategy for the development of the country’s entire SME sector. Such a strategy, which the paper has not extended into, remains to be an area for future research.